Ideologia judicial e política judiciária: Como os magistrados de apelaç\~ao responderam à reforma do sistema de medidas cautelares penais (Lei no 12.403/2011)? - Alexandre Samy de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper exploits the diversity of panels at the court of appeals in the state of Sao Paulo to address the role of career backgrounds and ideology in shaping the response of judicial decisions to a major criminal reform, enacted under Law 12,403/2011, which tightens the requirements for remanding of unsentenced prisoners in custody, by establishing priority of a whole range of non-custodial cautionary measures over remanding in custody. The Brazilian constitution reserves 80% of the seats in appellate courts to career judges, 10% to lawyers and 10% to prosecutors. In practice however, vacancies in panels coupled with backlogs have significantly increased participation of judges sitting by designation in appellate panels - who acted as rapporteurs in as much as 14% of all criminal appeals in S\~ao Paulo, between 2009-2013. Former lawyers and prosecutors are appointed by the state governor after nomination processes at the bar association and at the ministerial office. Judges sitting by designation are chosen at the discretion of the court's highest council and do not retain prerogatives of tenured appellate judges and are typically hired with the purpose of reducing backlogs. Their performance affects their chances of being promoted to the court of appeals, relatively to similar judges that have not been designated. Based on a large dataset of criminal appeals in the State S\~ao Paulo, Brazil, this study exploits the exogenous assignment of cases to rapporteurs, to identify the causal effects of career backgrounds on the response of appellate judges to satutory changes in remand custody. Estimates of treatment-effects, conditional on case characteristics and panel-specific fixed-effects, confirm that career judges and ex-lawyers respond favorably to defendants, in line with the statutory change. Former prosecutors and judges sitting by designation react contrarily the reform, responding unfavorably to defendants.
Keywords: K14; K41; 330; judicial decisionmaking; atitudinal model; judges sitting by designation; judicial appointments; remand custody